Autophagy in Viral Infection and Pathogenesis - Liang, Shan; Wu, Yun-Shan; Li, Dong-Yi; Tang, Ji-Xin; Liu, Hua-Feng (Frontiers in Cell and Developmental Biology, 2021)
As an evolutionarily conserved cellular process, autophagy plays an essential role in the cellular metabolism of eukaryotes as well as in viral infection and pathogenesis. Under physiological conditions, autophagy is able to meet cellular energy needs and maintain cellular homeostasis through degrading long-lived cellular proteins and recycling damaged organelles. Upon viral infection, host autophagy could degrade invading viruses and initial innate immune response and facilitate viral antigen presentation, all of which contribute to preventing viral infection and pathogenesis. However, viruses have evolved a variety of strategies during a long evolutionary process, by which they can hijack and subvert host autophagy for their own benefits. In this review, we highlight the function of host autophagy in the key regulatory steps during viral infections and pathogenesis and discuss how the viruses hijack the host autophagy for their life cycle and pathogenesis. Further understanding the function of host autophagy in viral infection and pathogenesis contributes to the development of more specific therapeutic strategies to fight various infectious diseases, such as the coronavirus disease 2019 epidemic.